A pesca extrativa marinha em Maceió-AL, sua cadeia produtiva e aspectos institucionais: fragilidades para uma pesca sustentável - Dapper, Cristiano Gil (2009)
This study examines how the institutional weaknesses have been affected the extractive marine fisheries in Maceió-AL, Brazil and its production chain, what has limited the sustainable development of the activity. A crisis in the Brazilian fisheries sector has been established since the 1980s, marked by public policies focused on increasing production without a proper concern with the fish stocks limits. Those policies, started by the end of the 1960s, were the causes of the stocks overfishing recorded from 1985, when successive decreases in annual production were observed, leading to destabilization of the entire fishing sector, which can be felt until the present. In this context, the extractive marine fisheries were examined in Maceió, between March 2007 and May 2009. The analysis starts with the fishing dynamics characterization, including a socio-economic approach. Subsequently, the research follows with a wider analytical view of the fisheries, by the characterization of the production chain according to the concept of Agribusiness System. Finally, within the production chain analysis, the institutional environment is evaluated, given a specificity of marine fishery, which refers to the common property rights of fish stocks. Economic theory shows that in such cases, the negative externalities - such as overfishing - appear easily, making the institutional role most important in the management through the establishment of rules for the use of fisheries resources. The current work shows that the marine fisheries in Maceió is all over of small scale, with family-owned vessels, motorized and non-motorized, which act indifferent types of fishing in terms of gears and target species. The production chain showed weakness mainly in the downstream linkages of the fisheries total catches, the stages of fish processing and marketing. Regarding institutional aspects, were found, although not widespread, weakened institutions with regard to physical structure, human and financial resources. Discontinuous and isolated actions prevailed over continuous and coordinated policies. These deficiencies observed locally combined with partial public policies, are the key elements that have hindering the sustainable development of fishing activity in Maceió. It is necessary to establish public policies that provide proper investments in the social, economic and environmental aspects, if the goal is the sustainable development of extractive marine fisheries.